Development of a Metacognition-Based E-Book Using 3D Pageflip to Enhance Polymer Chemistry Literacy in Coordination Polymerization Reactions - Syahri, Wilda; Yusnaidar, Yusnaidar (Pendidikan Kimia FKIP Universitas Jambi, 2024)
The development of a metacognition-based e-book using 3D Pageflip on coordination polymerization reaction materials aims to enhance students' polymer chemistry literacy. The Polymer course in the Chemistry Education Study Program covers various polymerization reactions essential for students in today's educational era. Polymers, including plastics, Styrofoam, nylon, and others, are crucial materials in various aspects of life. Due to the abstract nature of this subject, theoretical explanations are challenging for students to understand. A metacognition-based e-book is expected to assist students in self-learning, increasing flexibility in understanding polymerization reaction materials. This study employs the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation) and produces an e-book containing text, animations, videos, and music. Validation by experts indicates that the e-book is excellent in terms of content and design. Implementation among students shows that this e-book is effective in enhancing the understanding of coordination polymerization reactions. Thus, the e-book is expected to facilitate learning and improve students' polymer chemistry literacy. Keyword: Science literacy, polymer chemistry, polymerization reaction, coordination polymerization.